Signals of Distress: A Global Wave of University and College Closures - Mathews , Eldho; Altbach, Philip (International Higher Education, 2025)
The complex and difficult issue of university and college closures has received little attention but is of great importance, as many institutions do fail and close. The reasons are many, including demographic declines, leadership or governance failure, financial crisis, and others. Most vulnerable are private institutions, with warning signs including declining admissions, program cuts, and various governance issues. This crisis demands attention from academic communities and regulators to ensure institutional sustainability and quality.